LEGAL UNCERTAINTY OF THE RIGHT TO WORK FOR FOREIGNERS AND INDONESIAN SPOUSES WHO HOLD KITAS BASED ON LAW NUMBER 6 OF 2011 IN SEMARANG CITY - Febyola Alistya Senoaji (Law Research Review Quarterly, 2026)
This normative legal research analyzes the legal uncertainty regarding work rights for Foreign Workers (TKA) in mixed marriages with Indonesian Citizens (WNI) due to the disharmony between Law Number 13 of 2003 concerning Manpower in conjunction with Law Number 6 of 2023 concerning Job Creation (Job Creation Law) and Law Number 6 of 2011 concerning Immigration. The analysis of the norm hierarchy confirms that the Job Creation Law fails to impartially implement Article 42 letter e of the Immigration Law (KITAS mixed marriage), while systematization and synchronization indicate a conflict.special law versus general law which triggers dualism between RPTKA/IMTA and residence permits. Central Java BPS data of 165 foreign workers (2024) and the illegal Kendal case in 2025 illustrates this.that bewhich is contrary to that should Conclusion: The existing framework creates normative uncertainty. Recommendations include revising the Immigration Law (Article 42A, which exempts migrant workers from obtaining a permanent residence permit), a one-stop service Presidential Regulation, and a Ministry of Manpower-Immigration coordination task force to ensure legal certainty, protect families, and prioritize the national workforce in accordance with Article 28D of the 1945 Constitution and Constitutional Court Decision No. 168/PUU-XXI/2023.